PERBANDINGAN SIKLOKRIOTERAPI KOMBINASI DENGAN RETROBULBAR KLORPROMAZIN VS SIKLOKRIOTERAPI SAJA DALAM MENURUNKAN TEKANAN INTRAOKULAR DAN NYERI PADA GLAUKOMA TAHAP AKHIR - Muhammad Raditya Fadhil Fadhil; Retno Ekantini; Tatang Talka Gani; Krisna Dwi Purnomo Jati (Majalah Oftalmologi Indonesia, 2023)
Introduction: Patients with end-stage glaucoma often came with a painful blind eye. One of the managements is cyclocryotherapy (CCT) or retrobulbar chlorpromazine (CPZ). In this study, we aimed to evaluate the combined use of cyclocryotherapy and retrobulbar chlorpromazine versus cyclocryotherapy alone in reducing the intraocular pressure (IOP) and Visual Analog Scale (VAS) pain scores in end-stage glaucoma patients. Methods: Samples were taken from patients who enrolled in the Ophthalmology Clinic of Dr. Sardjito General Hospital from October 2021 to March 2022. Samples were then divided into 2 groups, the CCT+CPZ group received the combination of cyclocryotherapy and retrobulbar chlorpromazine and the CCT group received only cyclocryotherapy. IOP and VAS pain scores pre-operation and 30th-day post-operation were examined.  Results: Thirty-three patients were included in the CCT+CPZ group and 17 patients were included in the CCT group. The mean IOP and VAS pain scores 30th-day post-operation in the CCT+CPZ group were 22.6±10.3 mmHg and 1.6±1.3 vs pre-operation 44.9±19.5 mmHg and 7.9±1.7 (p=0.000). Patients in the CCT group also show a significant reduction in both mean IOP and VAS pain scores 31.4±16 mmHg and 2.6±2.3 vs pre-operation 54.4±7.4 mmHg and 8.4±2.1 (p=0.001). Both IOP and VAS pain scores at 30th-day post-operation were significantly lower in the CCT+CPZ group compared to the CCT group (p=0.030 and p=0.013, respectively). Conclusion: There were statistically significant differences between patients who received a combination of cyclocryotherapy and retrobulbar chlorpromazine in reducing the IOP and VAS pain score compared with patients who received only cyclocryotherapy.